Management of distal femoral diaphyseal fractures with string of pearls locking plate in dogs - KUMAR, K MANOJ; PRASAD, V DEVI; LAKSHMI, N DHANA; RAJU, N K B (The Indian Journal of Animal Sciences, 2018)
Distal femoral diaphyseal fractures in 6 dogs about 10–22 months old with body weight ranging from 12–25 kg were stabilized using String of Pearls (SOP) locking plates along with standard cortical and cancellous screws following standard AO/ASIF principles. Selection of appropriate size of plate and screws was according to body weight and type of fracture (2.7 mm plate for dogs below 12 kg body weight and 3.5 mm plate for dogs above 12 kg body weight) which provided good fracture stability. The outcome of fracture stabilization and healing was evaluated with lameness grading and radiography. Postoperatively, all the animals showed weight bearing with early functional limb usage of grade I lameness and good joint mobility in an average of 7 weeks. Functional outcome was good in four cases and excellent in two cases. The healing time in all the cases was 7–11 weeks. The fractures showed radiographically excellent postoperative healing with cortical union, absence of fracture lines and bridging callus. Based on present study, it was concluded that, String of Pearls (SOP) locking plates provided good stabilization of distal femoral diaphyseal fractures resulting in early limb ambulance and healing.